2018
DOI: 10.1051/0004-6361/201832887
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas in two companion cluster galaxies at z = 1.2

Abstract: Context. Probing both star formation history and evolution of distant cluster galaxies is essential to evaluate the effect of dense environment on shaping the galaxy properties we observe today. Aims. We investigate the effect of cluster environment on the processing of the molecular gas in distant cluster galaxies. We study the molecular gas properties of two star-forming galaxies separated by 6 kpc in the projected space and belonging to a galaxy cluster selected from the Irac Shallow Cluster Survey, at a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 110 publications
4
31
0
Order By: Relevance
“…In addition, a comparison with galaxies in the field, in clusters, and in other proto-clusters can provide insights into the role played by the environment. To this end, we collected CO data from the literature for galaxies in clusters (62 galaxies in 11 clusters, Wang et al 2018;Rudnick et al 2017;Stach et al 2017;Aravena et al 2012;Casasola et al 2013;Castignani et al 2018;Coogan et al 2018;Hayashi et al 2017;Webb et al 2017) and in proto-clusters (16 galaxies in four proto-clusters, Dannerbauer et al 2017;Ivison et al 2013;Tadaki et al 2014;Lee et al 2017), and of SMGs and AGN in the z = 1-3 redshift range (31 SMGs, 15 AGN, and 38 obscured AGN, Perna et al 2018). In order to represent normal star-forming galaxies and SB galaxies, we used the SFR-M rela-tion 5 from Speagle et al (2014), and the L CO − L IR relation from MS and SB galaxies as derived by Sargent et al (2014) 6 For estimating molecular gas masses, we converted all high transition CO luminosities to L CO(1−0) , when not available, using the median brightness temperature ratios derived by Bothwell et al (2013).…”
Section: Co Line Propertiesmentioning
confidence: 99%
“…In addition, a comparison with galaxies in the field, in clusters, and in other proto-clusters can provide insights into the role played by the environment. To this end, we collected CO data from the literature for galaxies in clusters (62 galaxies in 11 clusters, Wang et al 2018;Rudnick et al 2017;Stach et al 2017;Aravena et al 2012;Casasola et al 2013;Castignani et al 2018;Coogan et al 2018;Hayashi et al 2017;Webb et al 2017) and in proto-clusters (16 galaxies in four proto-clusters, Dannerbauer et al 2017;Ivison et al 2013;Tadaki et al 2014;Lee et al 2017), and of SMGs and AGN in the z = 1-3 redshift range (31 SMGs, 15 AGN, and 38 obscured AGN, Perna et al 2018). In order to represent normal star-forming galaxies and SB galaxies, we used the SFR-M rela-tion 5 from Speagle et al (2014), and the L CO − L IR relation from MS and SB galaxies as derived by Sargent et al (2014) 6 For estimating molecular gas masses, we converted all high transition CO luminosities to L CO(1−0) , when not available, using the median brightness temperature ratios derived by Bothwell et al (2013).…”
Section: Co Line Propertiesmentioning
confidence: 99%
“…We have assumed α CO = 4.36 M (K km s −1 pc 2 ) −1 , in agreement with the value adopted in this work, while for each galaxy we have assumed the excitation level adopted in the corresponding work. Similarly to Castignani et al (2018) we stress that by assuming the same α CO we aim at having comparable molecular gas mass estimates for the galaxies considered. According to our SFR< 6 SFR MS criterion the majority of the sources lie around the MS, which justifies the choice for α CO .…”
Section: Molecular Gas Diagramsmentioning
confidence: 99%
“…This work is the second reporting the results of a wider search for molecular gas in distant cluster galaxies (see also Castignani et al 2018). The paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Current observations of the CO emission line in clusters at these epochs show that cluster galaxies still have cold gas to fuel their star formation. However, these results are not yet statistically significant, and some results point toward higher molecular gas content in cluster galaxies with respect to the field and others to lower (Casasola et al 2013;Rudnick et al 2017;Noble et al 2017;Hayashi et al 2018;Coogan et al 2018;Castignani et al 2018). Molecular gas has also been detected in two protoclusters at z ∼ 2.5 (Chapman et al 2015;Wang et al 2016b).…”
Section: Introductionmentioning
confidence: 95%
“…At higher redshifts, the results are somewhat conflicting, as it also becomes more difficult to Lee et al 2017). Finally, at z < 1.5, for galaxies of the same mass and at the same redshift, cluster galaxies show lower amounts of molecular gas and thus, lower gas fractions (Jablonka et al 2013;Rudnick et al 2017;Lee et al 2017;Castignani et al 2018;Hayashi et al 2018). Some works have shown that at higher redshifts (z > 2), there is no difference in the gas fraction of cluster and field galaxies (Husband et al 2016;Dannerbauer et al 2017).…”
Section: Introductionmentioning
confidence: 95%